2017
DOI: 10.1007/s11604-017-0707-y
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous whole-body and breast 18F-FDG PET/MRI examinations in patients with breast cancer: a comparison of apparent diffusion coefficients and maximum standardized uptake values

Abstract: Prone breast imaging was more sensitive than whole-body PET/MRI for detection of breast cancers. Both SUVmax and ADCmean showed limited correlation with pathologic prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…In a study by Kong et al, only 4/10 (40%) subcentimeter breast cancers were seen on whole‐body PET/MRI . In a study by Sasaki et al, primary breast cancers were seen in all 94 patients on dedicated prone breast/MRI, while whole‐body PET‐MRI did not identify primary breast cancers in 7/94 (7%) patients . Therefore, in patients with elevated tumor markers and negative whole‐body imaging, consideration may be given to dedicated breast imaging.…”
Section: Distant Metastasesmentioning
confidence: 99%
“…In a study by Kong et al, only 4/10 (40%) subcentimeter breast cancers were seen on whole‐body PET/MRI . In a study by Sasaki et al, primary breast cancers were seen in all 94 patients on dedicated prone breast/MRI, while whole‐body PET‐MRI did not identify primary breast cancers in 7/94 (7%) patients . Therefore, in patients with elevated tumor markers and negative whole‐body imaging, consideration may be given to dedicated breast imaging.…”
Section: Distant Metastasesmentioning
confidence: 99%
“…For example, numerous reports suggested that PET parameters, such as the maximal standardized uptake value (SUV max ), depended on the histologic and biologic characteristics of the breast tumor [5] , [6] . Invasive tumors classified exhibit higher uptake than lower-grade tumors [5] , [6] , [7] . Furthermore, PET parameters can also predict behavior of BC [8] , [9] , [10] , [11] , [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Imaging methods, especially mammography, ultrasound and magnetic resonance imaging, play a fundamental role in the diagnosis of BC [2] . Nowadays, also positron emission tomography (PET) is increasingly used in BC [3] , [4] , [5] , [6] , [7] . It has been shown that PET besides detection of distant metastases can also provide additional information about tumor histopathology [5] , [6] , [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations